Musaeum Regalis Societatis, or, A Catalogue and Description of the Natural and Artificial Rarities Belonging to the Royal Society and Preserved at Gresham Colledge - Royal Society (Great Britain). Museum; Grew, Nehemiah; Gresham College (William Rawlins, 1681)
One of the earliest scientific societies, The Royal Society prided itself on following the precepts of Francis Bacon and taking an empirical approach to nature. The foundation of that approach was "matters of fact." Toward that end, the members of the Royal Society started a repository along the lines of 16th- and 17th-century "cabinets of curiosities," that is, a collection of man-made and natural rarities. Members contributed specimens and the collection grew rapidly. In the late 1670s, Nehemiah Grew, the Royal Society's secretary, began working on this catalog of the collection. In contrast to earlier such catalogs, Grew vowed to eschew the exotic and monstrous and refrain from repeating untruths from earlier sources. The title page and plates have been digitized.
Keywords: Royal Society (Great Britain). Museum; Natural history museums; Stomach; Digestive organs; Anatomy, Comparative; Natural history; Catalogs